1989 DC-10 crash: A cold case mystery solved. (May 2016) - McEvily, A.J.; Ishihara, S.; Mutoh, Y.
Highlights: In-surface fatigue cracks are detectable by fluorescent penetrant inspection (FPI). Sub-surface fatigue cracks are not detectable by FPI. NTSB: Cause of crash: an in-surface fatigue crack which was not detected by FPI. Our finding: Fatigue crack was sub-surface and therefore undetectable by FPI. Abstract: In 1989 a DC-10 aircraft crashed at the Sioux City, Iowa airport. The crash was the result of the catastrophic failure of the stage 1 fan rotor in the tail-mounted No. 2 engine due to fatigue cracking. No fatigue cracks had been detected over the 17 year life of the aircraft, although 6 fluorescent penetrant inspections (FPIs) had been carried out during this time period. The NTSB attributed the failure to an undetected fatigue crack which emanated from a defect on the surface of the disk bore. In contrast, we have concluded that, because of high surface compressive residual stresses as the result of shot-peening and the presence of hard alpha, all fatigue cracking was sub-surface, and as such could not have been detected by FPI.